(3ebGdI aj GdMhGS (B( (3hUhQgG hcjajI ehGbYgG hfSH HYVgG Edi HYV (B)s - (3YHO GddWja Hf jhSa Hf eMeO Hf Ydj GdHZOGOj, ehab GdOjf, hjYQa HGHf GddHGO, hHGHf fbWI,J (B629 (3g` s
(3ChdgG (B:s
(3bO YdeJ Cf GdMhGS NeS , hCfgG JTJQc ai EOQGc CYQGV GdCLSGe , hCf cdG efgG jNJU HfUa ef GdeOQcGJ hdG jTJQc GKfGf efgG ai Ufa hGMO ef GdeOQcGJ eYG s
(3BNQgG (B:s
(3hcGfJ MGSI GdSeY CNU GdMhGS hCNUgG HGdbhI GdfGWbI , cGfJ efaYJgG ai GdEfSGf CcKQ efgG ai SGFQ GdMjhGf , hcGf MX GdEfSGf CYXe ef MX SGFQ GdMjhGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B15s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B246 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(5/889) s
Keywords: (3GdWHs